The Fascinating World of Phosphanylphosphonates: From Acetylenic Phosphaalkenes to Reductive Aldehyde Couplings - Mai, Juri; Ott, Sascha (Synlett, 2019)
This account highlights the versatility of phosphanylphosphonates, which can be used for the preparation of phosphorus-containing π-systems and as reagents for the reductive coupling of carbonyl compounds to alkenes. Phosphanylphosphonates with metal fragments coordinated to the P-lone pair have been known for a long time and they have been used for the synthesis of phosphaalkenes by means of the phospha-Horner–Wadsworth–Emmons reaction. With the original aim of incorporating phosphorus heteroatoms into classical all-carbon ethynylethene scaffolds, we entered the field of phosphanylphosphonates with the discovery that these compounds engage in complex cascade reactions with acetylenic ketones, forming 1,2-oxaphospholes, cumulenes, and bisphospholes. Later, we synthesized the first metal-free phosphanylphosphonate, which reacts with aldehydes to yield phosphaalkenes, but gives phospholones when diacetylenic ketones are used as substrates. In the final part of the account, we outline our discovery and the development of an unprecedented carbonyl–carbonyl cross-coupling reaction. This protocol offers a straightforward method for the synthesis of nonsymmetric 1,2-disubstituted alkenes directly from two dissimilar aldehydes.1 Combining Acetylenes with Phosphaalkenes2 Synthetic Examples of Acetylenic Phosphaalkenes3 The Phospha-Horner–Wadsworth–Emmons Approach to Phosphaalkenes3.1 Metal-Coordinated Phosphanylphosphonates3.2 Mechanism of the Phospha-Horner–Wadsworth–Emmons Reaction3.3 The First Metal-Free Phosphanylphosphonate and Its Reactivity with Aldehydes4 Reactions with Acetylenic Ketones4.1 Metal-Coordinated Phosphanylphosphonate and Monoacetylenic Ketones4.2 Metal-Coordinated Phosphanylphosphonate and Diacetylenic Ketones4.3 Metal-Free Phosphanylphosphonate and Diacetylenic Ketones5 Metal-Free Phosphanylphosphonate as a Coupling Reagent for Aldehydes6 E-Alkenes by the Reductive Coupling of Two Aldehydes7 Conclusions and Outlook
Keywords: acetylenic phosphaalkenes; phosphanylphosphonates; bisphospholes; oxaphospholes; phospholones; alkenes